THE ESSENCE OF AGROECOTOURISM AND ITS ROLE IN THE DEVELOPMENT OF RURAL AREAS - Oybek Zoirovich Khaydarov (Journals Park Publishing, 2022)
The article discusses the essence of agroecotourism and its role in the development of rural areas. One of the most important strategic goals of state policy is to create conditions for the sustainable development of rural areas, the preservation of existing rural settlements in all the variety of existing forms of rural settlement. The development of tourism infrastructure in rural areas and, in particular, agro-tourism, can become one of the factors contributing to the diversification of the rural economy, increasing employment and incomes of the rural population; small business development, including in alternative areas of employment, and consequently, improving the quality of life in the countryside.
Keywords: agroecotourism, development, rural areas, historical and cultural heritage